Biosimilarity : The FDA Perspective - Niazi, Sarfaraz K.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The focus of this book is on how the US FDA will approve biosimilar drugs. The European scene is well developed with specific guidelines that are already in place. However, these guidelines do not apply to the thinking of the FDA in approving these products. The FDA is quite different from other regulatory agencies. With the US providing more than 50% of the worldwide market for these products, every serious manufacturer of biosimilar biological drugs should be targeting US approval of their products. Thus, this book is strictly on FDA approval strategy.
Current Status of Biosimilar Biological Products. The FDA Position. Biosimilarity Tetrahedron. Analytical and Functionality Similarity. Non-clinical Assessment. Clinical Pharmacology Assessment. Clinical Studies. Interchangeability Status. Comprehensive Presentation
Includes bibliographical references and index.
Also available in print format.
Keywords: Drugs -- Generic substitution; Pharmaceutical biotechnology -- United States; Pharmaceutical biotechnology; Biosimilar Pharmaceuticals; Drug Approval; Government Regulation; United States Government Agencies; MEDICAL / Pharmacology; Electronic books